2017
DOI: 10.15857/ksep.2017.26.4.239
|View full text |Cite
|
Sign up to set email alerts
|

The Comparisons of Blood Lactate Concentration and Removal Rate after Aerobic and Anaerobic Maximal Exercise

Abstract: This study examined blood lactate concentration and removal rate after aerobic and anaerobic maximal exercise test in sedentary middle-age women. METHODS: Ten sedentary middle-age women (aged 52.7±3.3 years) were performed after aerobic (Aero group) and anaerobic maximal exercise (Anaero group) test, VO2max test and Wingate test, by cross-over repeated design with biweekly. The blood was collected from cardinal veins at before and immediately after test for measurement of lactate and lactate dehydrogenase (LDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…The maximum blood lactic acid concentration varies depending on the subject, exercise method, and exercise intensity, increasing up to 25 mmol/L [ 28 ]. Simon et al [ 29 ] found that the higher the exercise ability, the higher the lactic acid diffusion rate, and the faster the increase in blood lactic acid concentration after exercise, the higher the exchange area as the density of capillaries through training increases [ 30 ]. As noted by Lecoultre et al [ 31 ], increased carbohydrate intake among athletes may elevate lactate levels, consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum blood lactic acid concentration varies depending on the subject, exercise method, and exercise intensity, increasing up to 25 mmol/L [ 28 ]. Simon et al [ 29 ] found that the higher the exercise ability, the higher the lactic acid diffusion rate, and the faster the increase in blood lactic acid concentration after exercise, the higher the exchange area as the density of capillaries through training increases [ 30 ]. As noted by Lecoultre et al [ 31 ], increased carbohydrate intake among athletes may elevate lactate levels, consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…시간에 따른 젖산 농도는 상승한다 (22) 혈중 젖산 농도는 시간 . 에 비례하여 증가하지 않지만 운동의 강도와 운동량에 따라 , 증가한다 (18) (19,28,29) 현재 현장에서는 최소 이상의 심폐 .…”
unclassified